Comparative study of keratinocyte primary culture methods from paediatric skin biopsies for RNA‐sequencing. Issue 11 (31st July 2022) - Salik, Déborah; El Kaderi, Yousra; Hans, Christine; Lefort, Anne; Libert, Frederick; Smits, Guillaume
Abstract: Background: Keratinocyte culture is a standard method used to study gene expression, cell differentiation and proliferation. Numerous protocols exist, however their application is frequently unsuitable for small specimens, such as 4‐mm punch skin biopsies. Aims: This study compared 3 different methods of keratinocyte culture from paediatric skin biopsies to evaluate which one ensures adequate cell growth for RNA extraction and sequencing. Materials and methods: Thirty‐six skin samples were obtained from 4‐mm punch skin biopsies from residual human body material from healthy children. They were cultured in vitro according to 3 different methods: enzymatic method, epidermis explant and direct explant method. Keratinocytes were characterized by immunocytochemistry using pan‐cytokeratin. RNA extraction was performed with RNeasy Mini kit. Quantity and quality of the extracted RNA was assessed to meet the requirements of library preparation for sequencing. Results: The direct explant method had largely shown its superiority over the two other methods, with a 100% success rate and an average of 15 days of culture. RNA extraction yielded a mean of 8545.85 ng of RNA per sample with an RQN of 10. Cover‐clip immunochemistry staining with pan‐cytokeratin had confirmed the absence of fibroblast contamination. Discussion: Although the enzymatic method is the most frequently used for keratinocyte culture, it is not suitable small samples required in dermatology. The direct explant method guarantees a high growth rate and the extraction of high quality RNA. Variation in the amount of RNA harvested are related to inter‐ and intra‐individual variations and to the conditions of the experiment. Conclusion: This study allowed to conclude that the direct explant method is the most efficient and easy method to ensure cell growth when the samples are from 4‐mm punch skin biopsies. This technique avoids fibroblasts contamination and obtains a sufficient quantity and quality of RNA to sequence it.